Pengaruh Latihan Circuit Training Terhadap Daya Tahan Aerobik Pada Kelas Ekstrakurikuler Sepak Bola SMA Negeri 1 Kabupaten Ketapang - Whisnu Catur Aji Pamungkas; Nevi Hardika (IKIP PGRI Pontianak, 2022)
This study aims to determine the effect of circuit training exercises on aerobic endurance in soccer extracurricular students at SMA Negeri 1 Ketapang. The method used in this study was an experiment with a population of 15 soccer extracurricular students. The research form used was the One Group Pretest-Posttest Design with pretests and posttests. The tests used in the research were the Multistage Fitness Test/Multistage Running Test. The data analysis technique used was the t test with a significance level of 5% or 0.05. The results showed that circuit training exercises had a significant effect with a tcount of 4.444 > ttable of 2.140. So it can be concluded that the circuit training exercises given for 12 meetings for 4 weeks had an effect on increasing the aerobic endurance of the soccer extracurricular students at SMA Negeri 1 Ketapang with an increase of 3%.